2018
DOI: 10.2147/ccide.s164403
|View full text |Cite
|
Sign up to set email alerts
|

Miswak users’ behavior model based on the theory of planned behavior in the country with the largest Muslim population

Abstract: BackgroundMaintaining proper oral hygiene has an influence on oral health. Religious obedience may influence individual behavior. According to Islamic religious guidance, as recommended by an Islamic role model, it is obligated to maintain oral health and the recommended tool to use is miswak.PurposeTo describe miswak users’ behavior based on the theory of planned behavior.Subjects and methodsThe population of this study was the students of As-Salafi Al-Fitrah Islamic Boarding School who used miswak regularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
(3 reference statements)
2
8
0
Order By: Relevance
“…PBC reflects the students' perception of how difficult it may be to engage in behaviors such as brushing and flossing. Previous studies in the field of oral health have proven that PBC is one of the most important factors influencing behavioral intention and behavior [15,26]. Consistent with the present study, Naseri-Salahshour et al found that an oral health intervention that target perceived behavioral control was efficacious in increasing tooth brushing among a sample of elementary school students in Iran [5].…”
Section: Discussionsupporting
confidence: 89%
“…PBC reflects the students' perception of how difficult it may be to engage in behaviors such as brushing and flossing. Previous studies in the field of oral health have proven that PBC is one of the most important factors influencing behavioral intention and behavior [15,26]. Consistent with the present study, Naseri-Salahshour et al found that an oral health intervention that target perceived behavioral control was efficacious in increasing tooth brushing among a sample of elementary school students in Iran [5].…”
Section: Discussionsupporting
confidence: 89%
“…8 Social and behavioral risk factors which have been identified as correlated to S-ECC include: low socioeconomic status, the availability of fluoridated water, the profile of the mother (level of education, own experience of caries, and degree of awareness of dental and oral health), dietary habits, inappropriate dental health behavior, and lack of access to dental health facilities. 9 These data confirmed that S-ECC predominantly affects the children of socially disadvantaged families, ethnic minorities, and individuals who live in less developed regions. 10 Caries may also cause damage to the adjacent tissue due to the spread of Streptococcus mutans leading to gingival or periodontal inflammation.…”
Section: Introductionsupporting
confidence: 64%
“…From the data was collected, the differences in behavior were analyzed before and after the intervention, the role-play stimulation, was given, wilcoxon signed rank test was used to compare the pre-test and post-test ordinal data intervention Overall statistical test was done on the significance level of α = 0.05 (Windows SPSS 21 program). If the statistical test shows the value of α ≤ 0.05 then there is a comparison between the previous data and after an intervention on moral development in children aged 8-9 years 10 .…”
Section: Discussionmentioning
confidence: 99%